Spherical Probing of Quiet Zone - Aldebrink, Filip; Carlsson, Rikard (My University, 2024)
Abstract This report furthers research antenna development, focusing on the crucial aspect of field probing in Compact Antenna Test Ranges. Traditional methods of field probing using Field Probe Scanners are examined, highlighting their limitations in terms of complexity, time consumption, and the inability to capture the full testing zone accurately. The study aims to explore the feasibility and advantages of employing Spherical Probe Scanning as an alternative to Field Probe Scanner-based techniques. By utilizing Spherical Probe Scanning, the report aims to streamline the measurement process, enhance accuracy, and enable comprehensive evaluation of antenna performance within a designated sphere. The methodology applied to process the measurement data, probe compensation and to analyze the Quiet Zone, which is of interest when using Field Probe Scanner or Spherical Probe Scanning, are presented. Relevant figures of the result, both theoretical and real measurements, and findings during the thesis, are discussed. The method at this stage of development did not allow the Quiet Zone to be analyzed from measurements, only from theoretical data. The problem was most likely the probe compensation, but the method shows promising features to be able to analyze the Quiet Zone using Spherical Probe Scanning.
Keywords: Keywords: Quiet Zone, Spherical Probe Scanning, SphericalWave Expansion, Probe Compensation, CATR, Anechoic Chamber, Field Probe Scanner, Ericsson.